The Influence of Organizational Culture Change, Integrity, and Transformational Leadership on Performance through Commitment as a Mediating Variable at the Functional Office of Bank Aceh Syariah in Banda Aceh City (International Journal of Scientific Research and Management (IJSRM), 2025)
This research aims to examine the influence of organizational culture change, integrity, and transformational leadership on performance through commitment as a mediating variable at the functional office of BAS in banda aceh city. The population in this study comprises all employees of the Bank Aceh Syariah (BAS) functional offices in Banda Aceh City. The research sample consisted of 230 respondents. The analysis method employed was PLS. The results indicate that organizational culture change have a positive effect on commitment, integrity has a positive effect on commitment, and transformational leadership has a positive effect on commitment. Furthermore, organizational culture change, integrity, and transformational leadership each have a positive effect on employee performance, and commitment also has a positive effect on employee performance. The mediation test results show that commitment partially mediates the effects of organizational culture change, integrity, and transformational leadership on employee performance at the functional offices of BAS in Banda Aceh City.